Empirical analysis of agricultural commodity prices - Öz, Mustafa Safa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
In the last ten years, Turkey has imported, on average, 60 percent of cotton used in the country from the USA. Hence, the relationship between cotton prices in Turkey and the USA is of significant importance. In this research, first, I test whether the law of one price (LOOP) rule holds for cotton prices in the USA and in Turkey, or not. Not only testing the LOOP is important, but testing the asymmetry between these two markets is important, as well. For testing, I use (i) Threshold Autoregression model (TAR), (ii) Momentum Threshold Autoregression model (M-TAR), and (iii) MTAR with consistent estimate of threshold level. I verify the presence of negative asymmetry between these markets. In other words, cotton market in Turkey shows greater response to falling prices than to rising prices in the USA cotton market. The relations between agricultural commodity prices and crude oil prices are also very important in the economics literature. As a second research question, I investigate the relationship between crude oil prices, cereal prices (corn and wheat), and cotton prices in major international markets considering the impacts of the financial crisis in 2008. I find that there exists a cointegration relationship between crude oil prices and wheat prices. Also, I find evidence of a cointegration relationship between corn prices and cotton prices, corn prices and wheat prices, cotton prices and wheat prices with regime shifts. The timings of regime shifts are as expected. This leads to the conclusion that the financial crisis in 2008 has changed the relationship between commodity prices.
Keywords: Cotton -- Turkey.; Cotton -- Prices.; Agriculture -- Economic aspects -- Turkey.